A fish supper and a chippy smile. love, hardship and laughter in a South East London fish-and-chip shop /: love, hardship and laughter in a South East London fish-and-chip shop. Chapters 1-5 : Part one, (2015) - Kemp, Hilda; Kemp, Cathryn
No abstract available